Special information meeting about the P.O.U.M. trial (invitation) (1938)
024_0004_001 INDEPENDENT LABOUR PARTY 35, St. Bride Street, London, E.C.4. You are invited to a SPECIAL INFORMATION MEETING about the P.O.U.M. TRIAL to be hold at the national Trade Union Club, 24, New Oxford Street, W.C., at 8 p.m. on Wednesday, October 19th. JOHN McNAIR who is now in Paris and in direct touch with Barcelona, will give a detailed statement about the proceedings of the trial. Fenner Brockway will preside. 292/946/24/4